ETIKA PANCASILA SEBAGAI PANDUAN MORAL BAGI REMAJA DALAM KEHIDUPAN BERMASYARAKAT - Aira Putri Vaneza; Sariah Sariah; Dila Puspita Sari; Rangga Andestiko (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The ethics of Pancasila, which are divinity, humanity, unity, democracy, and justice, are founded on both excellent and terrible assessments of these ideals. Building Indonesian society's character on moral and ethical principles is the goal of Pancasila as an ethic. The techniques employed are the digital research method and the library research method. According to the study's findings, Pancasila is a fundamental component of Indonesian society, serving as a foundation for ethics and a means of regulating proper conduct for its residents.